Mortality and Survival Analysis in COVID-19 Patients: Hematological and Biochemical Study - Rashid, Daban Sabah; Ghafoor, Dlzar Dlshad; Salih, Karzan Jalal (Sulaimani Journal for Pure and Applied Sciences, 2023)
Severe acute respiratory syndrome (SARS-CoV-2) that causes novel coronavirus pneumonia (COVID-19) interacts with the receptor (angiotensinconverting enzyme) on the lung epithelial cells and leads to rapid deterioration of human health if no care is provided, hence risk identification of the case severity is important. The objective of the present study is to analyze the relationship between blood parameters and the severity, survival, and mortality of COVID-19 patients based on the hematological and biochemical abnormalities associated with Iraqi COVID-19 patients. A prospective multicenter observational study has been done on a total of 103 patients admitted to different hospitals between November 1, 2021, and April 1, 2022. Among these 30 (29.1%) patients died, 81% died within two weeks of admission to the hospital, and 73 patients (71.9%) survived. An independent sample t-test revealed a significant difference in the tests including AST, ALT, D-dimer, urea, creatinine, and chloride ion between the dead and survived patients, while there was a non-significant difference when these parameters were compared (age, BMI, CPR, PT, INR, APTT, WBC, LYM, GRA, HGB, RBC, ESR, Creatinine, Na and K ions). Crosstab’s study showed that most death (80%) were at ages >60 years, 53.3% of the deaths were having normal BMI and only 10% were obese. Three models for logistic regression were performed to test if the available data set is more effective than the null hypothesis, all three tests yield a similar conclusion that the available data can be used to check the risk factors in COVID-19 patients.
Keywords: SARSCoV2; COVID19; severe pneumonia; hematologicalparameter; biochemical parameter